Komunikasi Instruksional Di Kelas Yoga Club Health Fatimah Kota Serang - Indrianti Azhar Firdausi (Universitas Serang Raya, 2018)
Yoga is a sport that is much in demand by sports lovers today even though yoga is always identified with meditation and religious rituals. Moreover, the emergence of yoga in the city of Serang could bring concern to the local community which is thick with a devout Islamic religion, but over time yoga was accepted and had space by opening a yoga class at the Fatimah Health Club in Serang City. The implementation of the vinyasa yoga exercise instruction prioritizes breathing arrangements with the aim of harmony of body and soul. This study uses the concept of instructional communication and cognitive learning theory to find out how to think, instruction to interpret yoga and the implementation of yoga instruction through breathing, posture of movement to the use of the language of yoga instruction. Use The research method is a case study with data collection techniques through interviews, observation and documentationKeywords: Yoga, Instructional communication, cognitive learning